Establishment and implementation of the nursing order system based on the Gui Meifen's nursing records model of syndrome differentiation (桂梅芬辨证施护病历模式下医院信息管理护嘱系统的构建与实施) - GUO Hui (郭慧); HAO Li (郝丽); ZHAO Guomin (赵国敏); HE Hong (何红); LIU Lijuan (刘丽娟); ZHOU Gexia (周革霞) (Association of Integrative Nursing, 2023)
This paper summarized the establishment and implementation of the hospital information (HIS) nursing order system based on the Gui Meifen's nursing records model of syndrome differentiation Based on HIS of Beijing Hospital of Traditional Chinese Medicine and Gui Meifen Traditional Chinese Medicine Nursing Inheritance Studio of Beijing Administration of Traditional Chinese Medicine, the nursing order system for discharged patients was designed and developed. A personalized and comprehensive TCM nursing discharge order system was constructed, including diet care, emotional care, medication care, exercise regimen, rehabilitation and return visit. The nursing order system is conducive to the inheritance of Gui Meifen's nursing records model of syndrome differentiation, construction of nurses team, promotion of health education standardization, and improvement of patients' satisfaction. (本研究总结了基于桂梅芬辨证施护病历模式构建医院信息管理(HIS)护嘱系统并开展实践的相关经验。HIS护嘱系统包含饮食护理、情志调护、用药护理、运动养生、康复及复诊等方面的个性化、全面居家中医护理指导, 该系统的应用有利于促进中医护理的传承发展和护士队伍的建设, 推进健康教育规范化, 提高患者满意度。)